Dual‐Cure Coatings: Spiroorthoesters as Volume‐Controlling Additives in Thiol–Ene Reactions. Issue 4 (18th January 2019) - Marx, Philipp; Romano, Angelo; Fischer, Roland; Roppolo, Ignazio; Sangermano, Marco; Wiesbrock, Frank
Abstract: Most thiol–ene systems exhibit shrinkage during cross‐linking, potentially resulting in micro‐cracks and delamination. Oligocyclic monomers like spiroorthoesters (SOEs), on the contrary, show expansion during the ring‐opening polymerization. In this communication, a photocurable thiol–ene system composed of a trifunctional thiol, a bisfunctional allyl‐bisphenol A compound, and an SOE compound bearing one olefin function shows expansion in the range from −3.07 to +1.70 vol% if the SOE content is increased from 0–30 wt%. Network formation can be accomplished under visible light if a radical as well as a cationic photoinitiator (dual‐cure mechanism) and a sensitizer are used. The elasticity of the cured resin increases upon the addition of the SOE; correspondingly, the glass‐transition temperature shows a (minor) decrease from 16 to 3 °C. A tailor‐made combination of the allyl‐bisphenol A compound (90 wt%) and the SOE (10 wt%) yields networks that are volume‐neutral during curing. Abstract : Bicyclic spiroorthoesters undergo volumetric expansion upon cationic (double) ring‐opening polymerization . They can be used as additives in polymerizations to control the shrinkage that conventional polymerizations exhibit; if the spiroorthoesters bear olefinic structural motifs, they can be covalently attached into thiol–ene networks, while the shrinkage/expansion can be tailored.